Iatrogenic Infective Endocarditis in Hemodialysis Patients: A Case Report and Review of the Literature - Ali Oullaï; Edouard Cubilier; Mohamed Tayeb Salaouatchi; Maxime Taghavi; Yasmin Zouggari; Joëlle Nortier; Maria Do Carmo Filomena Mesquita (Case Reports in Nephrology)
Foreign bodies such as implanted cardiac devices are susceptible to infections and may be involved in infective endocarditis. Exposure to pathogens, by frequent use of intravascular accesses for hemodialysis (i.e., catheters or fistulas), combined with high rates of degenerative heart valve diseases in hemodialysis patients, both favor the development of infective endocarditis in this population. The mitral and aortic valves are predominantly implicated in endocardial infections. The involvement of both mitral and tricuspid valves is rare in the general population but can occur in hemodialysis patients with implanted cardiac devices. Infective endocarditis is associated with high morbidity and mortality rates among hemodialysis patients, mostly because of the complications of septic emboli. Prevention, prophylaxis, and early diagnosis of endocarditis can be lifesaving in this fragile population. We report a case of right and left heart methicillin-sensitive Staphylococcus aureus endocarditis with cerebral septic emboli in an elderly hemodialysis patient carrier of an arteriovenous fistula and an ipsilateral nonleadless pacemaker.